2021
DOI: 10.3390/sym13112012
|View full text |Cite
|
Sign up to set email alerts
|

Identification Method of Wheat Cultivars by Using a Convolutional Neural Network Combined with Images of Multiple Growth Periods of Wheat

Abstract: Wheat is a very important food crop for mankind. Many new varieties are bred every year. The accurate judgment of wheat varieties can promote the development of the wheat industry and the protection of breeding property rights. Although gene analysis technology can be used to accurately determine wheat varieties, it is costly, time-consuming, and inconvenient. Traditional machine learning methods can significantly reduce the cost and time of wheat cultivars identification, but the accuracy is not high. In rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 23 publications
0
8
1
Order By: Relevance
“…The neural network model trained on the canopy data was not able to make similarly large increases in prediction of genotype over the GNB model, indicating that seed data is better suited for distinguishing genotypes than canopy measurements. This differs from the findings of Gao et al 13 , who found that images of wheat during tillering and flowering enabled more accurate classification of wheat genotypes than images of seeds. However, that study also used RGB images as input instead of decomposed spectral/morphological data (as is used in this study), which may account for some of these differences.…”
Section: Discussioncontrasting
confidence: 99%
“…The neural network model trained on the canopy data was not able to make similarly large increases in prediction of genotype over the GNB model, indicating that seed data is better suited for distinguishing genotypes than canopy measurements. This differs from the findings of Gao et al 13 , who found that images of wheat during tillering and flowering enabled more accurate classification of wheat genotypes than images of seeds. However, that study also used RGB images as input instead of decomposed spectral/morphological data (as is used in this study), which may account for some of these differences.…”
Section: Discussioncontrasting
confidence: 99%
“…They furthermore used average accuracy as a metric over an imbalanced inference set, which is not in accordance with the literature [ 35 ]. Gao et al [ 36 ] achieved an accuracy of 99.51% in differentiating 30 wheat cultivars at the flowering (most mature) stage. This is very impressive, considering the present study suffered the most error when trying to discriminate between the various cereal classes.…”
Section: Discussionmentioning
confidence: 99%
“…When cereals are treated as a grouped cereal class, they are easily set apart from the rest of the crops, but when assessing the differences between the cereals, the structure of the fruit, stem, and leaf organs can look too similar. Indeed, the approach in Gao et al [ 36 ] yields such good results exactly because the model is designed to pick up on the subtle differences between the varieties. In the present case, grouping the cereals together would produce a M-F1 of 88.2 without and 90.4 with quadrant filtering, which is 12.5 and 14.7 points higher than the achieved result.…”
Section: Discussionmentioning
confidence: 99%
“…the best classification accuracy of 95.68% attributed to DensNet201 architectur Javanmardi et al [115] successfully classified nine corn seed varieties based on a VGGpre-trained CNN model. Gao et al [116] proposed a CNN based variety classificatio model for multiple growth periods of wheat. In the study, the CMPNet achieved hig classification precision at the seed stage of wheat (Specific performance index shown Figure 5) based on ResNet and SENet.…”
Section: Crop Seed Variety Classificationmentioning
confidence: 99%